Characterization of stone tesserae from "The Indian Triumph of Dionysus" Mosaic (Casignana, Reggio Calabria, Italy). Issue 1 (1st April 2022) - Rovella, N; Musella, M; Barca, D
Abstract: The archaeological site of Casignana (Reggio Calabria) represents one of the most important Roman sites of Southern Italy thanks to its extension and refinement of its mosaics such as the "Indian Triumph of Dionysus". Its stylistic complexity is related also to the wide range of polychrome stone tesserae used. For this reason, a minero-petrographic and geochemical characterization of some tesserae was carried out by Polarized Optical Microscopy (POM), Scanning Electron Microscope (SEM), and Electron probe microanalyzer combined with wavelength dispersive X-ray spectroscopy (EPMA-WDS). The results suggested the heterogeneity of the stone tesserae in terms of petrographic features and the probable provenance from both local and not sites.